Визначення кількості сонячної енергії, що сприймається сферичним трубчастим колектором - Matsevytyi Yu.M.; Safonov M.O.; Bushtets Y.M. (General Energy Institute of the National Academy of Sciences of Ukraine, 2021)
Spherical solar tubular collector (SSTK) was invented in A. Pidgorny IPMash. as an alternative to the solar flat collector to convert the radiant energy of the Sun into heat. To understand the efficiency of a collector, it is important to know how much energy it can take.A methodology for calculating the amount of heat perceived by the collector has been developed. The surface area of a spherical tubular collector illuminated by the Sun using proposed methodology was determined. The amount of heat received by the solar collector for each day of the year was estimated. The total amount of heat received by SSTK in Kharkiv during the year was defined.